Moral re-armament: toward a better understanding of the society-corporation relationship before the emergence of "corporate social responsibility". Issue 3 (28th October 2020) - Dent, Eric B.; Randall, Craig
Abstract : Purpose: This study aims to introduce moral re-armament's (MRA) role as a mediator in several labor/management disputes in industries primarily in the 1940s and 1950s. In this study, MRA was guided by a social responsibility framed in language that was a precursor to corporate social responsibility (CSR). This study features the case of the Miami-based airlines serving Latin America, who had experienced the longest airline labor strike to that date. Design/methodology/approach: In this study, both artifacts and literary interpretations are used to inform an institutional-theory-based approach to a broad social movement, one player in that movement and its impact on an industry. Actions at one time can be shown to relate to activity and behavior at another time (Wadhwani and Bucheli, 2014). Thus, this paper has combined these perspectives in the approach to historically examine a precursor phenomenon of CSR. Findings: MRA's approach shared some methods, such as story-telling, with modern change management. This paper proposes that other methods that were important for that historical context played a significant role in MRA's success. Today, these methods are no longer used. These include "intimacy" (MRA employees lived with members of labor and management while they were mediating), "theater" (they showed plays to all of those involved) and confessional sharing (their training was mostly a series of testimonies by those who previously were combative, but became collaborative when they accepted MRA's principles). Originality/value: This historical case may inspire those promoting CSR to expand their methods to have even greater success today.